1992
DOI: 10.1172/jci116080
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of proteins of the complement system in human skin.

Abstract: The complement system participates in the immune recognition of foreign antigens, many of which may penetrate the skin by physical injury or transcutaneous adsorption. In this study, we examined the presence of complement components and complement regulatory proteins in the human skin and cultured human keratinocytes. Immunofluorescence studies showed C3, Factor B, decay accelerating factor, the C3b receptor (CR1), and C3d receptor (CR2), distributed among cells of the epidermis as well as on cultured keratino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 49 publications
3
32
0
Order By: Relevance
“…In control tissue, C3d was found diffuse in the epidermis as has been described earlier 21,22 ( Figure 1A, arrow I). Also, C3d positivity was found in the horn layer ( Figure 1A, arrow II).…”
Section: Resultssupporting
confidence: 80%
“…In control tissue, C3d was found diffuse in the epidermis as has been described earlier 21,22 ( Figure 1A, arrow I). Also, C3d positivity was found in the horn layer ( Figure 1A, arrow II).…”
Section: Resultssupporting
confidence: 80%
“…DAF, MCP, and CD59 are present on keratinocytes in the human skin as seen in situ in previous immunohistochemical studies (Dovezenski et al, 1992;Venneker et al, 1994). This study shows surface expression of DAF, MCP, and CD59 on cultured keratinocytes.…”
Section: Discussionsupporting
confidence: 80%
“…Keratinocytes have C-regulatory proteins embedded in their membranes to prevent this damage (Sayama et al, 1991;Dovezenski et al, 1992;Venneker et al, 1994). These include decay accelerating factor (DAF; CD55), membrane cofactor protein (MCP; CD46), and CD59 (Liszewski et al, 1996).…”
mentioning
confidence: 99%
“…This ability to activate complement has been suggested as a mechanism responsible for the inflammation associated with seborrheic dermatitis (SD). The proteins involved in the initial steps of the alternative complement pathway are known to be present in the skin (117), and complement-mediated inflammation is associated with many dermatoses, including bullous pemphigoid (198), acne vulgaris (390), and psoriasis (410). Immunohistochemical studies of SD have found that deposits of C3 are present in the lesions, localized solely around the collections of Malassezia cells, and are absent from uninvolved skin (334).…”
Section: Activation Of the Complement Cascadementioning
confidence: 99%